Studies on Schismatoglottideae (Araceae) of Borneo LXIV: Another new species for the Schismatoglottis Patentinervia Clade from the Rejang Basin, Sarawak - Sin Yeng, Wong; Aisahtul, Wardi; Peter C., Boyce (International Aroid Society, 2018)
Schismatoglottis gangsai S. Y. Wong, Aisahtul & P. C. Boyce is described and illustrated from Kapit, C Sarawak, as a new species for the Schismatoglottis Patentinervia Clade and Basin is provided. Recognition of S. gangsai takes the Patentinervia Clade to 10 described species, of which 8 have been described since 2000.